Letter (copy) - Hunt, Charles
1936-11-16 041-0012-003 Hospital Britanico, Granen, Huesca (Aragon). November 16th 1936. The Spanish Medical Aid Committee, 24, New Oxford Street, London, W.1. Comrades, Consequent upon the arrival of two of four new vehicles here, we, the members of the transport section of the Unit have decided to make representations to you on the following points. When the original Unit came to Spain to offer medical assistance to the Spanish workers three Vehicles were bought to serve out here as Ambulances. Of these only one was equipped with stretcher runways and supports, the other two being two-ton commercial trucks. At this period the Spanish Government were using many trucks themselves as Ambulances and the vehicles we were able to add were received gratefully. The position, however, changed as soon as it was possible to organise and militarise the factory producing the commercial vehicles for the Government with the result that they were soon producing first-class Ford ambulances properly sprung and fitted. By this time it was apparent that our vehicles were totally unsuitable for withstanding the conditions prevailing at the front and this was conveyed to the Committee. The only result of the request of the Unit at the Front for equipped and sprung ambulances was the arrival in Spain of two ex-L.C.C. ambulances 12 and 8 years old respectively, which came to be the laughing-stock of the Unit on account of their antiquated design and complete uselessness. In this connection may we add that the Austin lasted here for two or three days and the Talbot never reached here. One of the drivers of these vehicles, Poole, forwarded a report strongly condemning the action of the responsible persons on the Committee and this report was taken back to England by the Committee's liaison officer, Clark. A second Unit was then formed in London and Farr, who should have been aware of the conditions here, and was aware of the uselessness of two-ton Renault trucks, was made responsible for the purchase of further transport. Instead of obtaining two, or even one first-class equipped ambulance he again purchased two-ton Renault trucks and one light van, three of which were fitted with sprung stretcher units. These trunks are next to useless and the effect they have had on the Authorities here is to lead them to believe that we are maintained by incompetent and irresponsible persons who have no understanding of the situation. We are afraid that we ourselves are forced to view the action of the Committee in the same light when the reports of experienced drivers and technicians are ignored. / / I suppose via Clark. 292/946/41/12(iii)